A design to cost system for innovative product development. - Shehab, Essam; Abdalla, Hassan S. (Professional Engineering Publishing, 2002)
This research paper presents a prototype object-oriented and rule-based system for product cost modelling and design for automation at an early design stage. The developed system comprises a computer aided design (CAD) solid modelling system, a material selection module, a knowledge-based system (KBS), a process optimization module, a design for assembly module, a cost estimation module and a user interface. The system development process has passed through four major steps: constructing the knowledge-based and process optimization system; developing a design for assembly module; integrating the KBS with both a material selection database and the CAD system; developing and implementing a fuzzy logic approach to generate reliable estimation of cost and to handle the uncertainty in the cost estimation model that cannot be addressed by traditional analytical methods. Two manufacturing processes, namely machining and injection moulding processes, were considered in the developed system. The main function of the system, besides estimating the product cost, is to generate initial process planning, including the generation and selection of machining processes, their sequence and their machining parameters, and to recommend the most economical assembly technique for a product and provide design improvement suggestions based on a design feasibility technique. In addition, a feature-by-feature cost estimation report is generated using the proposed system to highlight the features of high manufacturing cost. Two case studies were used to validate the developed system.
Keywords: concurrent engineering; manufacturing cost modelling; process optimization; object-oriented programming; feature-based CAD; fuzzy logic